PENGUKURAN EFEKTIVITAS OPERASIONAL TERHADAP IMPLEMENTASI ERP PADA PT. ZZR - Fedora, Brenda; Setiawan, Johan (Journal of Business, Management, and Social Studies, 2021)
The objective of this study is to understand what impact ERP has on the company and help evaluate ERP implementation using the DeLone & McLean method. This research uses Quantitative method research distributed to 104 end users. The results of the study found points that after measuring the effectiveness of ERP operational activities at PT ZZR and analysis of the data obtained, it can be concluded that the factors that affect the effectiveness of the implementation are the quality of the information produced, the level of user satisfaction is good and has a net benefit for ERP users. From the effectiveness measurement, it is expected that the company can find out that the costs and time spent are proportional to the effectiveness and benefits obtained by the company and assist the company in evaluating the implementation of ERP in the company.